Investigation of the Seismic Behavior of a Historical Masonry Minaret Considering the Interaction with Surrounding Structures - Erdogan, Yildirim Serhat; Kocaturk, Turgut; Demir, Cihan (TAYLOR & FRANCIS LTD, 2019)
This study examines the seismic behavior of the minaret of the well-known historical structure Sultan Ahmed Mosque under strong earthquake motion. Despite their slenderness and height, minarets are towers with well-established earthquake resistance. In general, these structures were constructed adjacent to the main structure and/or its components. Hence, it is expected that the dynamic behavior of the minarets is influenced by the dynamic characteristics of the adjacent structures as well as the contact conditions. In the presented study, the dynamic behavior of the M6 minaret of the Sultan Ahmed Mosque, which is in contact with the portico that surrounds the courtyard of the mosque, is considered. Ambient vibration tests were conducted on site in order to identify the individual and coupled vibration modes of the minaret and the portico. A finite/discrete model was developed and seismic analysis was carried out. The comparative study reveals considerable differences in responses of different models under strong and very strong earthquake motion.
Keywords: Seismic Analysis; Historical Masonry Structures; Finite/Discrete Element Method; Dynamic Interaction; Experimental Modal Analysis; ONLY MODAL IDENTIFICATION; DISCRETE ELEMENT MODEL; DYNAMIC IDENTIFICATION; ADJACENT BUILDINGS; SYSTEMS; Engineering; Geology